FOREIGNIZATION AND DOMESTICATION STRATEGIES IN INDONESIAN TRANSLATIONS OF TAO TE CHING - Pauw Budianto (LITERA, 2019)
As a cultural dialogue, translation has two main ways: foreignization or domestication. These two translation methods are also reflected in the Indonesian translations of the Tao Te Ching. This paper attempts to analyze the performance of these two translation methods in nine books of Indonesian Tao Te Ching translations, including the title of the book and the main philosophical terms (Dao, De, Ziran, Wuwei). This is a qualitative descriptive study, with literature survey as the main method of data collection. The results show that the tension between the two translation methods in the nine versions of Indonesian translations of the Tao Te Ching are different, reflecting a complex phenomenon. Translation of the title of the book, mostly used combination between foreignization and domestication strategies, kept the book name Tao Te Ching and subtitles that expressed what kind of book was the Tao Te Ching in the translator’s mind. The translations of Dao had a trend of foreignization, while the translations of De were exactly the opposite. The translations of Ziran mostly used domestication strategy, and the translations of Wuwei had a trend of foreignization in some newest translations. Keywords: foreignization, domestication, Indonesian translations, Tao Te Ching STRATEGI FOREIGNISASI DAN DOMESTIKASI DALAM TEKS-TEKS TERJEMAHAN TAO TE CHING BERBAHASA INDONESIA AbstrakSebagai suatu bentuk dialog antarkultur, penerjemahan terutama memunyai dua cara, yakni foreignisasi dan domestikasi. Fenomena kedua metode penerjemahan ini juga muncul dalam teks-teks terjemahan Tao Te Ching berbahasa Indonesia. Artikel ini menganalisis bagaimana fenomena kedua metode penerjemahan ini terjadi di dalam teks-teks terjemahan tersebut yang terdiri atas sembilan versi berbeda dari berbagai tahun terbitan, terutama terkait penerjemahan judul buku dan penerjemahan konsep-konsep utama dalam Tao Te Ching (Dao, De, Ziran, Wuwei). Penelitian ini merupakan penelitian diskriptif kualitatif dengan studi literatur sebagai metode utama pengumpulan data. Hasil penelitian menunjukkan bahwa tensi antara kedua metode penerjemahan tersebut dalam teks-teks terjemahan Tao Te Ching berbeda satu dengan yang lain menampilkan fenomena yang cukup rumit. Penerjemahan judul buku kebanyakan menggunakan perpaduan foreignisasi dan domestikasi mempertahankan judul asli Tao Te Ching dan judul kecil yang menunjukkan buku seperti apa Tao Te Ching di benak penerjemah. Penerjemahan kata Dao memunyai kecenderungan foreignisasi, penerjemahan kata De sebaliknya lebih cenderung domestikasi. Penerjemahan kata Ziran lebih banyak menggunakan domestikasi, penerjemahan kata Wuwei ada kecenderungan foreignisasi di beberapa karya terjemahan terbaru. Kata Kunci: foreignisasi, domestikasi, teks Tao Te Ching, Bahasa Indonesia